Ten Simple Rules for Effective Computational Research - Osborne, James; Bernabeu, Miguel; Bruna, Maria; Calderhead, Ben; Cooper, Jonathan; Dalchau, Neil; Dunn, Sara-Jane; Fletcher, Alexander; Groen, Derek; Knapp, Bernhard; Mirams, Gary; Pitt-Francis, Joe; et al. (PLoS Computational Biology, 2014)
In order to attempt to understand the complexity inherent in nature, mathematical, statistical and computational techniques are increasingly being employed in the life sciences. In particular, the use and development of software tools is becoming vital for investigating scientific hypotheses, and a wide range of scientists are finding software development playing a more central role in their day-to-day research. In fields such as biology and ecology, there has been a noticeable trend towards the use of quantitative methods for both making sense of ever-increasing amounts of data [1] and building or selecting models [2].